ANALISA KESESUAIAN KAWASAN TRANSIT BLOK M, JAKARTA TERHADAP KRITERIA KONSEP TOD (TRANSIT ORIENTED DEVELOPMENT) - Muhammad Afif Arsyad; Ketut Dewi Martha Erfi Handayeni (PLANNERS INSIGHT : URBAN AND REGIONAL PLANNING JOURNAL, 2019)
Located in CDB Jakarta, Blok M is one of most strategic area in Jakarta that developed by TOD principles. TOD concept is an approach to develop a city that focuses on station areas. The characteristic of TODs are high density, mixed land use, and pedestrian friendly. This research used spatial query analysis to identify level of congruence Blok M as an area that developed by TOD`s concept. The result of this research implies that congruence Blok M as TOD`s area is 85,215% only. It also shows that density in Blok M area is high already but in the other hand diversity and pedestrian ways design in Blok M still below standart of TODs.